The heroes of Great Moravia – native or foreign? - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2009)
The aim of the article is to analyse chronicles from the Latin cultural sphere in order to determine the scope and nature of the presence of characters and motifs related to Great Moravia. The author focuses on Croatian, Czech and Hungarian chronicles, looking at, among others, Pop Duklanin's Latopis, Kosmas' Chronicle and Hungarian historiography. The method of critical comparative analysis of narrative sources was used, taking into account hagiographic texts and secular historiography. The results of the research indicate that the Great Moravian tradition was widely present in the written and oral culture of the Central European region, although its reception varied from country to country. In Hungarian historiography, Moravia appeared as a foreign entity, and the memory of it survived mainly in oral legends about Svatopluk. Croatian chroniclers included some themes (e.g. the activities of Cyril), but without clearly indicating their Moravian origin. Czech historiography, on the other hand, treated Great Moravia as the direct predecessor of its own statehood and Christianity. The memory of Great Moravia was an important factor in shaping the political and religious identity of the region, although its interpretation was subject to local conditions and ideological needs.